Health Effects Related to Wind Turbine Sound: An Update - Irene van Kamp (International Journal of Environmental Research and Public Health, 2021)
Commissioned by the Swiss Federal Office for the Environment, an update of an earlier narrative review was prepared for the literature published between 2017 and mid-2020 about the effects of wind turbine sound on the health of local residents. Specific attention was hereby given to the health effects of low-frequency sound and infrasound. The Netherlands Institute for Public Health and the Environment and Mundonovo sound research collected the scientific literature on the effect of wind turbines on annoyance, sleep disturbance, cardiovascular disease, and metabolic effects, as well as mental and cognitive impacts. It also investigated what is known about annoyance from visual aspects of wind turbines and other non-acoustic factors, such as the local decision-making process. From the literature study, annoyance again came forward as the most important consequence of sound: the louder the sound (in dB) of wind turbines, the stronger the annoyance response was. The literature did not show that “low-frequency sound” (sound with a low pitch) results in extra annoyance on top of normal sound. Results of scientific research for other health effects are either not available or inconsistent, and we can conclude that a clear association with wind turbine related sound levels cannot be confirmed. There is evidence that long-term effects are related to the annoyance people experience. These results confirm earlier conclusions. There is increasing evidence that annoyance is lower when people can participate in the siting process. Worries of residents should be addressed in an early stage, by involving them in the process of planning and decision making.